Structural characterization of recombinant crustacyanin subunits from the lobster Homarus americanus - Ferrari, M.; Folli, C.; Pincolini, E.; McClintock, T. S.; Roessle, M.; Berni, R.; Cianci, M. (Acta Crystallographica Section F Structural Biology and Crystallization Communications, 2012)
Crustacean crustacyanin proteins are linked to the production and modification of carapace colour, with direct implications for fitness and survival. Here, the structural and functional properties of the two recombinant crustacyanin subunits H(1) and H(2) from the American lobster Homarus americanus are reported. The two subunits are structurally highly similar to the corresponding natural apo crustacyanin CRTC and CRTA subunits from the European lobster H. gammarus. Reconstitution studies of the recombinant crustacyanin proteins H(1) and H(2) with astaxanthin reproduced the bathochromic shift of 85-95 nm typical of the natural crustacyanin subunits from H. gammarus in complex with astaxanthin. Moreover, correlations between the presence of crustacyanin genes in crustacean species and the resulting carapace colours with the spectral properties of the subunits in complex with astaxanthin confirmed this genotype-phenotype linkage.